Optimal Path Planning With Minimum Inspection Teams and Balanced Working Hours For Power Line Inspection - Hu, Zhao-Long; Deng, Yuan-Zhang; Peng, Hao; Han, Jian-Min; Zhu, Xiang-Bin; Zhao, Dan-Dan; Wang, Hui; Zhang, Jun (Frontiers in Physics, 2022)
Power lines inspection plays a significant role in the normal operation of power systems. Although there are many researches on power lines inspection, the question about how to balance the working hours of each worker and minimize the total working hours, which is related to social fairness and maximization of social benefits, is still challenging. Experience-based assignment methods tend to lead to extremely uneven working hours among the working/inspection teams. Therefore, it is of great significance to establish a theory framework that minimizes the number of working teams and the total working hours, as well as balances the working hours of inspection teams. Based on two real power lines in Jinhua city, we first provide the theoretical range of the minimum number of inspection teams, and also present a fast method to obtain the optimal solution. Secondly, we propose a transfer-swap algorithm to balance working hours. Combined with intelligent optimization algorithm, we put forward a theoretical framework to balance the working hours and minimize the total working hours. The results based on the two real power lines verify the effectiveness of the proposed framework. Compared with the algorithm without swap, the total working hours obtained by transfer-swap algorithm is shorter. In addition, there is an interesting finding, for our transfer-swap algorithm, the trivial greedy algorithm has almost the same optimization results as the simulated annealing algorithm, but the greedy algorithm has an extremely short running time.